PENGGUNAAN MODEL GI (GROUP INVESTIGATION) PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Rafhi Febryan Putera; Zahratul Qalbi (Jurnal Pendidikan, 2020)
This research is motivated by the initial reflection of researchers who conduct observation of teaching and learning activities in Paninjauan Elementary Schools elementary schools, that the civic education learning was dominated by the teacher using conventional learning method in learning low when the daily test exam and the final exam semeseter. The purpose of this study is to describe how learning planning, learning implementation, and learning outcomes. The approach used in this research is a qualitative approach and a quantitative approach with four stages, namely learning planning, learning implementation, learning observation, and learning reflection. The subjects used in this study were grade IV students of SDN 11 Paninjau Agam Regency. From the data analysis, it was found that the Group Investigation (GI) type of cooperative learning model was proven to improve student learning outcomes. This can be seen from the percentage of completeness learning Cycle I of 58.6 and in the second cycle increased to 72.25.